The Controversy Surrounding Artificial Intelligence Regulation in Higher Education in Indonesia - Abriadi Muhara; Hasmawaty; Sitti Nurhidayah Ilyas; Bonita Mahmud (Asian Journal of Applied Education (AJAE), 2026)
This study examines the controversy surrounding the regulation of Artificial Intelligence (AI) in Indonesian higher education and its implications for academic ethics and adaptive governance in the digital era. The research employs a qualitative approach through interviews, observations, and document analysis to explore the integration of AI in academic practices. The findings indicate three main issues: the increasing integration of AI and digital learning systems in teaching and learning processes, the growing number of research and innovation initiatives related to AI within universities, and the lack of clear national regulations governing AI usage in higher education. These findings highlight the need for adaptive governance frameworks and policy guidelines to ensure that AI technologies are utilized responsibly while maintaining academic integrity and supporting sustainable educational transformation.